Analysis of Syrinx and Its Associations: A Retrospective Study - Javaji Ravi Prasad; Harsha U; Nidhi B Raj (Asian Journal of Medical Radiological Research, 2019)
Background: Syrinxis described as a cavitary enlargement of the spinal cord. It is a common reason for neurosurgical referral. The aetiology of syrinx is multiple andit is associated with other brain and spinal cord conditions,while some are not associated with any other conditions. Subjects and Methods: We retrospectively collected data of cases diagnosed with syrinx in the department of radiodiagnosis in Rajarajeswari Medical college, Bangalore and studied the conditions associated with syrinx. Results: A total of 37 cases were analysed. The spinal cord levelsmost commonly associated with syrinx were C5, C6, T1 and L1 vertebral levels. Arnold Chiari malformation type 1 was the most common condition associated with syrinx. Conclusion: It was concluded from the present study that syrinx was more common in males than females with mean age of presentation of 36 years. The cervical spinal cord level was most commonly involved followed by thoracic and lumbar spinal cords. ACM type 1 was the most common associated condition. It becomes important for radiologist to look for syrinx in cases diagnosed with associated conditions, so that subtle and mild forms of syrinx are not missed and their growth or expansion in spinal cord be evaluated in follow up MRI studies.